"Rule of Law" in a Party-State: A Conceptual Interpretive Framework of the Constitutional Reality of China. Issue 1 (20th March 2015) - LI, Ling
Abstract This article identifies and conceptualizes the structural features of the Party-state and proposes a "dual normative system" as a framework to interpret the constitutional reality of China. This framework has four components: (1) structural integration of the Chinese Communist Party (CCP or the Party) and the state; (2) reserved delegation of authority to the state; (3) bifurcation of state decision-making processes; and (4) cohabitation of the two normative systems: one of the Party and one of the state. This article demonstrates that the political reforms in China since the 1980s have not separated the power of the Party and the state, but have created an increasingly institutionalized dual normative system that is more complex compared with the previous fused system, yet more pliable to adjustments and more open to different interpretations, including to that of the "Party-state constitutionalism", which interprets the "rule of law" as compatible with the rule of the Party.